2009
DOI: 10.1093/nar/gkp683
|View full text |Cite|
|
Sign up to set email alerts
|

A universal description for the experimental behavior of salt-(in)dependent oligocation-induced DNA condensation

Abstract: We report a systematic study of the condensation of plasmid DNA by oligocations with variation of the charge, Z, from +3 to +31. The oligocations include a series of synthetic linear ε-oligo(l-lysines), (denoted εKn, n = 3–10, 31; n is the number of lysines equal to the ligand charge) and branched α-substituted homologues of εK10: εYK10, εLK10 (Z = +10); εRK10, εYRK10 and εLYRK10 (Z = +20). Data were obtained by light scattering, UV absorption monitored precipitation assay and isothermal titration calorimetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 81 publications
10
62
1
Order By: Relevance
“…After incubation at room temperature for ~ 1 hour, the solution was centrifuged at 16000 × g for 10 min and the DNA absorbance at 260 nm of the supernatant was measured. Critical concentrations were observed to decrease approximately by an order of magnitude for each additional charge as seen by others (35, 36). The cation concentration used in the bathing PEG-salt solution for the osmotic stress force measurements was 2 to 6 fold higher than the critical concentration.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…After incubation at room temperature for ~ 1 hour, the solution was centrifuged at 16000 × g for 10 min and the DNA absorbance at 260 nm of the supernatant was measured. Critical concentrations were observed to decrease approximately by an order of magnitude for each additional charge as seen by others (35, 36). The cation concentration used in the bathing PEG-salt solution for the osmotic stress force measurements was 2 to 6 fold higher than the critical concentration.…”
Section: Methodssupporting
confidence: 74%
“…Ando and coworkers (43, 44) have found that arginine peptides are much more efficient in precipitating DNA than the analogous ornithine peptides. At the low salt concentrations used here, 10 mM Tris, pH 7.5, the binding of most tetra- and higher valent ions is close to stoichiometric (35). None-the-less, Thomas and coworkers (36, 45) at similar low salt conditions have found that considerably more tetra-lys 4+ was necessary for DNA condensation than spermine 4+ and that significantly more penta-lys 5+ was necessary than several +5 analogs of spermine.…”
Section: Discussionmentioning
confidence: 98%
“…An important problem in this context is related to understanding the mechanism of DNA compaction and self-assembly. In the nucleus of eukaryotic cells, the DNA molecule exists as a hierarchically ordered structure formed by the nucleosome core particles consisting of complexes of DNA with histone proteins, and there are strong indications [1][2][3][4] that the stability of chromatin (and, thus, DNA transcription and replication) is modulated by electrostatic interactions. The problem of polyelectrolyte and DNA condensation in solution has a long history of experimental studies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We tried to select complexation conditions that would prevent higher aggregation. Salt counterions are known to shield the charges of polycations, thus weakening their interac tion with DNA [22]. Polyethyleneimine interacts with DNA to produce small particles at low salt concentra tions and large aggregates at high salt concentrations [22].…”
Section: Resultsmentioning
confidence: 99%
“…Salt counterions are known to shield the charges of polycations, thus weakening their interac tion with DNA [22]. Polyethyleneimine interacts with DNA to produce small particles at low salt concentra tions and large aggregates at high salt concentrations [22]. To determine if this is true for H2A TAT, its com plexes with DNA were obtained in 20 mM NaCl at a mass ratio of 1 : 25, and the salt concentration in the suspension was then increased in a stepwise manner.…”
Section: Resultsmentioning
confidence: 99%